Interpretacijos: Vilniaus universiteto bibliotekos rankraščių atvejis - Girininkaitė, Veronika (Bibliotheca Lituana, 2018)
[full article and abstract in Lithuanian; summary in English] The article is dedicated to the expression silva rerum, which is quite new in Lithuanian science discourse. It is sometimes used to name a peculiar kind of egodocuments, the handwritten family or personal notebooks. The etymology, interpretation variations of this expression and it‘s suitability to become a scientific term are being discussed. The history of the term shows, that the meaning of it changed a lot in various epochs. The manuscript codexes of Manuscript Department of Vilnius University Library, which were described by some historians as silvae rerum are reviewed in order to verify or falsify this proposed term. The results of the research show that the name should not be applied to all of those manuscripts, because, as case studies show, some of them do not fit to the existing descriptions of genre. Also it is stated, that there is a need to specify the definition of the family notebooks, and also to create a proper Lithuanian terminology, adequate for the types of existing local egodocuments.